2009
DOI: 10.1149/1.3109573
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Gadolinium Oxide Nanocrystal Memory with Optimized Rapid Thermal Annealing

Abstract: Gadolinium oxide nanocrystal ͑Gd 2 O 3 -NC͒ memories treated by postdeposition rapid thermal annealing were investigated. Bandgap offset performed by a crystallized Gd 2 O 3 -NC dot surrounded by amorphous Gd 2 O 3 dielectrics is successfully demonstrated and proven by the transmission electron microscopy images and electron diffraction pattern. The Gd 2 O 3 -NC memory exhibits a hysteresis memory window of 4 V and NC dot density of more than 8.5 ϫ 10 11 cm −2 . In addition, the formation of Gd 2 O 3 -NC and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…The RTA treatment of amorphous Gd 2 O 3 film is an effective and simple method to form Gd 2 O 3 -NCs, which are used as Si-based and heterostructure GaN/AlGaN-based charge trapping devices [19,20]. It has been demonstrated that the capacitance-voltage sweep measurement yields a large memory window of the Gd 2 O 3 -NC memories.…”
Section: Introductionmentioning
confidence: 99%
“…The RTA treatment of amorphous Gd 2 O 3 film is an effective and simple method to form Gd 2 O 3 -NCs, which are used as Si-based and heterostructure GaN/AlGaN-based charge trapping devices [19,20]. It has been demonstrated that the capacitance-voltage sweep measurement yields a large memory window of the Gd 2 O 3 -NC memories.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 illustrates the room temperature data retention characteristics of RTA treated ZrO 2 NC-based CTF memory cells before (solid symbols) and after 10 5 W/E cycles operation (open symbols). The charge loss is defined as [20]:…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a 4-nm-thick SiO 2 film was thermally grown on a silicon wafer by furnace in O 2 ambient, which was fabricated for comparison and denoted as C. After that, an 8-nm-thick Gd 2 O 3 layer was deposited by using the RF sputtering with a 99.9% pure gadolinium (Gd) target in argon (Ar) and oxygen (O 2 ) mixed ambient at room temperature. The flow ratio of Ar to O 2 was 7:1 under a chamber pressure of 10 mtorr and an RF power of 100 W. After the Gd 2 O 3 film had been formed, the samples were subjected to rapid thermal annealing (RTA) at 900°C for 30 s in N 2 ambient to form Gd 2 O 3 -NCs [14]. A 10-nm-thick SiO 2 layer was deposited by plasma-enhanced chemical vapor deposition (PECVD) system to act as a blocking oxide.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the gadolinium oxide (Gd 2 O 3 ) nanocrystal, a rare earth metal oxide material, has been proposed to exhibit superior memory properties [14][15][16][17][18][19]. The Gd 2 O 3 -NCs can be formed by the crystallized Gd 2 O 3 dots with small band-gap surrounded by the amorphous Gd 2 O 3 film with large band-gap [20], which is different from the traditional NCs embedded in SiO 2 matrix [6,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%